KEWAJIBAN NOTARIS DALAM MENJALANKAN PRINSIP TATA KELOLA KANTOR NOTARIS YANG BAIK DAN PROFESIONAL(GOOD CORPORATE PUBLIC NOTARY) MENURUT UU NOMOR 30 TAHUN 2004 JUNCTO UU NOMOR 2 TAHUN 2014 TENTANG JABATAN NOTARIS - Adi Prasetiyo; Gunarto Gunarto (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2017)
Notary in performing his duties acting as public servant in the affairs of making the deed of agreement which is the will of the parties who want to make it. In order to improve notary services as much as possible one of them is with the notary's office itself. Notary obligation in implementing good corporate public notary principles must be consistent with Law Number 30 Year 2004 juncto Law Number 2 Year 2014 regarding Notary Position and referring to the Notary Code of Ethics, as well as from inventory office, employees, documentation and services to clients. The constraints often faced in carrying out the principles of office governance is arising from the notary itself and from employees, where the notary is involved in a criminal case that causes punishment and employees who act dishonestly in carrying out their work, thus causing harm to office management itself and become disorganized in its management.Keywords: notary, office